LANGUAGE CHANGE: A SOCIOLINGUISTIC STUDY - Achmad A. Al Barqy; Dwi Setya Rini; Dela A. Langu (Adisam Publisher, 2025)
Language change is a natural and dynamic process influenced by internal linguistic factors and external societal forces such as technology, culture, and interaction. This paper explores the phenomenon of language change, addressing its definition, causes, mechanisms of spread, and implications for communication and society. It delves deeper into sociolinguistic theories, historical linguistic evidence, and the role of globalization in accelerating these transformations. Practical implications for language education and cultural preservation are also discussed.